Column Studies on Effect of Phosphate Immobilization on Removal of Metals from Stormwater Runoff in Bioretention Cell - Demir, V.; Bin-Shafique, S. (Asian Journal of Chemistry, 2013)
Batch studies indicated that low cost native materials such as loam soil, juniper mulch, hardwood mulch, pine mulch and sawdust performed efficiently as media in bioretention cell for removal of copper and lead from stormwater runoff. Juniper mulch performed best in batch studies was used in column studies. Column studies suggested that the presence of phosphate has a pronounced effect on metal immobilization. This is due to the formation of metal phosphates that have extremely low solubility. The remaining metals were adsorbed on bioretention media of the bioretention cell. Breakthrough adsorption and desorption curves for lead and copper were measured in presence and absence of phosphate immobilization. Copper reached a breakthrough curve in around 20 days and lead in 30 days. Column studies showed that in all samples addition of phosphate also decreased the leaching of lead and copper back to aqueous solution consistent with lead and copper immobilization.